Effects of high-intensity interval training on cardiopulmonary fitness and blood pressure of obese adolescent girls in China - Soh, Kim Geok; Wazir, Mohd Rozelee; Wenping, Wang (Eletrical Syetems, 2024)
Objective: The objective of this study is to evaluate the effects of 12 weeks high-intensity interval training(HIIT) on the cardiopulmonary fitness (CPF)and blood pressure (BP)of obese adolescent girls in China. Methodology: This was a single-center, randomized, repeated-measures controlled trial (RCT), 44 girls were randomized into 1 interventional groups (HIIT group) or 1 control group (no training). In the HIIT group, set 100% MAS as the load intensity, and 50% MAS as interval intensity. A 15-second running (intensity of 100% MAS), followed by a 15-second walking (intensity of 50% MAS), which was regarded as 1 bout, each set includes 8 bouts, 4 sets each time, 3 minutes’ rest between sets, 25 minutes of interval training time, plus warm-up and cooling time, the total training time was 35 minutes. Intervention period is 12 weeks; the frequency was three times a week. In the dependent variable of this study, there were 5 indicators, including body weight(BW), maximum oxygen uptake (VO2max), resting heart rate (HRrest), systolic blood pressure (SBP), and diastolic blood pressure (DBP). All dependent variables were measured at baseline, 6th weeks and 12th week. To examine the effect of the intervention on the outcomes of interest, Generalized Estimating Equation (GEE) was used. Results: 39 girls completed the 12-week intervention. 19 in the HIIT group and 20 in the control group. Results of GEE showed BW, HRrest, SBP and DBP in the HIIT group decreased and VO2max increased statistically over time. Conclusion: 12 weeks HIIT can improve cardiopulmonary fitness and blood pressure of obese adolescent girls in China.